PENGARUH FIRM SIZE DAN GROWTH OPPORTUNITY TERHADAP CASH HOLDING DAN FIRM VALUE - Liestyasih, Luh Putu Erma; Wiagustini, Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.10.TAHUN 2017DO - 10.24843/EEB.2017.v06.i10.p07, 2017)
This research aims to determine the effect of firm size and growth opportunity to cash holding and firm value. Manufacturing companies that listed in Indonesian Stock Exchange are used as population. Annual ?nancial data of 38 ?rms from manufacturing companies listed on Indonesian Stock Exchange from 2013 to 2016 examined as sample. Path analysis technique used to analysis hypothesis of  the research by SPSS software. The results showed that: firm size and growth opportunity had positive and significant impact on firm value. Firm size had negative and significant impact on cash holding. Growth opportunity had positive and significant impact on cash holding. Cash holding had positive and significant impact on firm value. Cash holding mediated the effect of growth opportunity on firm value significantly.